PENGARUH LEVERAGE, PERTUMBUHAN PERUSAHAAN, AUDIT TANURE, DAN OPINI AUDIT TERHADAP MANAJEMEN LABA (STUDI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2017) - Wijayanti, Dina Eka; Triani, Ni Nyoman Alit (Jurnal Akuntansi AKUNESA, 2020)
This study aims to provide empirical evidence related to the effect leverage, growth, audit tanure and opini audit on earning management. The research sample is mining companies in Indonesia Stock Exchange periode 2013-2017 consisted of 100 companies. The data analysis technique used in this study is multiple regression analysis. Hypothesis test results indicate that leverage and growth has a negative influence on earning management. Meanwhile, audit tanure and opini audit have no effect on earning management.